Modified silicon negative electrode material, preparation method of modified silicon negative electrode material, negative electrode plate and battery
By covering the carbon material layer on the surface of the silicon negative electrode material and forming a polyacrylic layer to form a two-dimensional dense network structure, the problem of high expansion rate of the silicon negative electrode material is solved, and the energy density and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411907122.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
AI Technical Summary
The volume expansion of the silicon negative electrode material during lithium embedding is large, resulting in rupture of the SEI film, breaking and falling off the particles, thereby reducing battery performance.
Using a modified silicon negative electrode material, a carbon material layer is coated on the surface of the silicon negative electrode particles and a polyacrylic acid layer is formed on the surface of the carbon material layer to form a two-dimensional dense network structure to reduce the expansion rate of the silicon negative electrode particles and at the same time improve the conductivity of the negative electrode sheet.
It effectively reduces the expansion rate of silicon negative electrode material, improves the conductivity of the negative electrode sheet, extends the cycle life of the battery and increases the energy density.
Smart Images

Figure CN119742334A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a modified silicon negative electrode material, a method for preparing the modified silicon negative electrode material, a negative electrode sheet and a battery. Background Art
[0002] With the rapid development of the lithium-ion battery industry, how to prepare lithium-ion batteries with high energy density has become the main development direction of the market. The energy density of the battery is closely related to the positive and negative electrode materials. At present, the negative electrode materials used in the market are mostly graphite, silicon negative electrode materials, etc. Among them, the theoretical capacity of graphite is 372mAh / g, while the theoretical capacity of silicon is 4200mAh / g, which is about 11 times that of graphite. Silicon negative electrode materials have become the main development direction of negative electrode materials for high energy density batteries. However, the volume expansion coefficient of silicon negative electrode materials when embedded with lithium is large, about 3 times that of graphite. It is easy to have problems such as rupture of the SEI film of negative electrode particles, breakage and shedding of negative electrode particles during the cycle process, which can easily lead to reduced battery performance. Summary of the invention
[0003] The purpose of the present application is to provide a modified silicon negative electrode material, a preparation method of the modified silicon negative electrode material, a negative electrode sheet and a battery. The use of the modified silicon negative electrode material can effectively improve the problem of large expansion rate of the silicon negative electrode material, which is beneficial to improving the performance of the battery.
[0004] The present application provides a modified silicon negative electrode material, comprising a core and a shell layer, wherein the core comprises silicon negative electrode particles and a carbon material layer coated on the surface of the silicon negative electrode particles, and the shell layer is a polyacrylic acid layer, and the polyacrylic acid layer is coated on the surface of the carbon material layer.
[0005] The embodiment of the present application provides a modified silicon negative electrode material, which uses a polyacrylic acid network layer as a coating layer to coat the surface of the inner core. On the one hand, the carboxyl groups on the long chains of polyacrylic acid react chemically with the modified groups on the surface of the inner core to form chemical bonds such as ester groups, thereby forming a two-dimensional dense network on the surface of the inner core, and the inner core is wrapped therein. The closed network structure has a strong elastic contraction force, thereby reducing the expansion rate of the silicon negative electrode particles in the inner core. On the other hand, polyacrylic acid, as a polyanionic polymer, has good ionic conductivity, which can effectively improve the conductivity of the negative electrode sheet prepared therefrom, so that the assembled battery has both high energy density and long cycle life.
[0006] In some embodiments, the polyacrylic acid layer is chemically grafted onto the surface of the carbon material layer.
[0007] In some embodiments, the material of the silicon negative electrode particles includes at least one of pure silicon, silicon carbon, and silicon oxygen.
[0008] The present application also provides a method for preparing a modified silicon negative electrode material, comprising:
[0009] Providing or preparing pretreated particles, the pretreated particles comprising a core and a grafting group grafted on the surface of the core, the core comprising a silicon negative electrode particle and a carbon material layer coated on the surface of the silicon negative electrode particle, the grafting group being grafted on the surface of the carbon material layer and capable of reacting with a carboxyl group;
[0010] preparing a mixed raw material, the mixed raw material comprising pretreated particles and polyacrylic acid salt, wherein the polyacrylic acid salt is coated on the surface of the pretreated particles to form a polyacrylic acid layer;
[0011] The mixed raw materials are heated to prepare a modified silicon negative electrode material, wherein the carboxyl group of the polyacrylic acid layer reacts with the grafted group under heating conditions.
[0012] In the preparation method of the modified silicon negative electrode material provided in the embodiment of the present application, a grafting group is formed on the surface of the carbon material layer in the inner core, and then the grafting group is used to react with the carboxyl group in the polyacrylic acid layer to achieve chemical grafting of the polyacrylic acid layer to the surface of the inner core. Wherein, the polyacrylic acid layer is coated on the surface of the inner core. On the one hand, the carboxyl group on the long chain of polyacrylic acid in the polyacrylic acid layer can react chemically with the surface modification group of the inner core to form a chemical bond such as an ester group, thereby forming a two-dimensional dense network on the surface of the inner core, and the inner core is wrapped therein to form a dense network structure. The closed network structure has a strong elastic contraction force, thereby reducing the expansion rate of the silicon negative electrode particles in the inner core. On the other hand, polyacrylic acid, as a polyanionic polymer, has good ionic conductivity, which can effectively improve the conductivity of the modified silicon negative electrode material, thereby effectively improving the conductivity of the negative electrode sheet prepared by it, so that the assembled battery takes into account both high energy density and long cycle life.
[0013] In some embodiments, the grafted group includes at least one of an epoxy group, an amino group, and a hydroxyl group.
[0014] In some embodiments, the grafted group is an epoxy group, and the step of preparing the pretreated particles includes: pretreating the inner core with a raw material including an oxidant and an epoxy compound.
[0015] In some embodiments, the mass ratio of oxidant:epoxide compound=1:(1-2).
[0016] In some embodiments, the pretreatment temperature is 60°C to 120°C.
[0017] In some embodiments, in the step of heating the mixed raw materials, the heating temperature is 100°C to 200°C.
[0018] In some embodiments, based on the mass of the mixed raw materials, the mass fraction of the polyacrylate is 1% to 2%.
[0019] In some embodiments, the molecular weight of the polyacrylic acid in the polyacrylic acid layer is 100,000 to 500,000.
[0020] An embodiment of the present application also provides a negative electrode sheet, including a negative electrode current collector and a negative electrode layer covering the surface of the negative electrode current collector, wherein the material of the negative electrode layer includes a modified silicon negative electrode material, and the modified silicon negative electrode material is the modified silicon negative electrode material as described above, or is a modified silicon negative electrode material prepared according to the preparation method of the modified silicon negative electrode material as described above.
[0021] An embodiment of the present application also provides a battery, comprising a positive electrode sheet and the negative electrode sheet as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A schematic diagram of the structure of a modified silicon negative electrode material provided in an embodiment of the present application;
[0024] Figure 2 Schematic diagram of the preparation principle of silicon negative electrode material when the grafted group is epoxy group. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0026] The present application provides a battery, including a positive electrode sheet, a negative electrode sheet and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet. The battery can be made by stacking the positive electrode sheet, the separator and the negative electrode sheet, and then winding or laminating them.
[0027] Specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode layer covering the surface of the positive electrode current collector. Among them, the positive electrode layer can cover one side surface or both sides of the positive electrode current collector along the thickness direction. Exemplarily, the positive electrode current collector can be aluminum foil. The positive electrode layer includes a positive electrode active material. In the embodiment of the present application, the battery is described by taking a lithium-ion battery as an example. In this case, the positive electrode active material can be selected from one of lithium cobalt oxide, lithium iron phosphate, and nickel cobalt oxide.
[0028] The negative electrode sheet includes a negative electrode current collector and a negative electrode layer coated on the surface of the negative electrode current collector. The negative electrode layer may be coated on one side surface or both sides of the negative electrode current collector along the thickness direction. Exemplarily, the negative electrode current collector may be copper foil or carbon-coated aluminum foil. The negative electrode layer includes a negative electrode active material. When the negative electrode active material is a silicon negative electrode material, the silicon negative electrode material may have a silicon expansion problem, which may easily cause the performance of the battery to decrease. At present, the main method for reducing the expansion rate of silicon negative electrode materials is surface carbon coating, that is, coating a carbon material layer on the surface of silicon negative electrode particles, but there are problems such as low silicon content (limited room for energy density improvement) and unclear improvement effect.
[0029] In order to solve the above technical problems, an embodiment of the present application provides a negative electrode layer, and the negative electrode layer includes a modified silicon negative electrode material. The structure of the modified silicon negative electrode material is specifically described below.
[0030] See also Figure 1 , Figure 1 A schematic diagram of the structure of a modified silicon negative electrode material 100 provided in an embodiment of the present application.
[0031] The modified silicon negative electrode material 100 includes a core 10 and a shell layer, wherein the shell layer covers the outer surface of the core 10 .
[0032] Specifically, the inner core 10 includes silicon negative electrode particles 11 and a carbon material layer 13 coated on the outer surface of the silicon negative electrode particles 11. Among them, the material of the silicon negative electrode particles 11 is a silicon-based material containing silicon elements and can be used for the negative electrode of the battery. Exemplarily, the material of the silicon negative electrode particles 11 includes at least one of pure silicon, silicon carbon and silicon oxygen. The embodiment of the present application does not limit the material of the silicon negative electrode particles 11. It can be understood that the carbon material layer 13 can be prepared by the existing carbon coating method, for example, the carbon material layer 13 can be prepared by chemical vapor deposition, pyrolysis, etc., which will not be repeated here.
[0033] The shell layer is coated on the outer surface of the carbon material layer 13 to achieve the shell layer coating the outer surface of the core 10. The shell layer is a polyacrylic acid layer 30. In the embodiment of the present application, the polyacrylic acid in the polyacrylic acid layer 30 is chemically grafted on the surface of the carbon material layer 13, that is, the polyacrylic acid is connected to the carbon material layer 13 through a chemical bond. Exemplarily, the molecular weight of the polyacrylic acid in the polyacrylic acid layer 30 is 100,000 to 500,000. Specifically, the molecular weight of the polyacrylic acid in the polyacrylic acid layer 30 can be 100,000, 200,000, 300,000, 400,000, 500,000, and any value between the above values.
[0034] The embodiment of the present application provides a modified silicon negative electrode material 100, which uses a polyacrylic acid layer 30 as a coating layer to be coated on the surface of the core 10. On the one hand, the carboxyl groups on the long chains of polyacrylic acid in the polyacrylic acid layer 30 react chemically with the surface modification groups of the core 10 to form chemical bonds such as ester groups, thereby forming a two-dimensional dense network on the surface of the core 10, and the core is wrapped therein to form a dense network structure. The closed network structure has a strong elastic contraction force, thereby reducing the expansion rate of the silicon negative electrode particles 11 in the core 10. On the other hand, the polyacrylic acid layer 30 has conductivity, which can effectively improve the conductivity of the modified silicon negative electrode material 100, thereby facilitating the improvement of the conductivity of the prepared negative electrode sheet, and further facilitating the realization of high energy density and long cycle life of the assembled battery.
[0035] The present application also provides a method for preparing the modified silicon negative electrode material 100, including:
[0036] S1. Provide or prepare pretreated particles, the pretreated particles comprising an inner core 10 and a grafted group grafted on the surface of the inner core 10, the inner core 10 comprising a silicon negative electrode particle 11 and a carbon material layer 13 coated on the surface of the silicon negative electrode particle 11, the grafted group is grafted on the surface of the carbon material layer 13 and can react with a carboxyl group.
[0037] Exemplarily, the grafted group includes at least one of an epoxy group, an amino group, and a hydroxyl group.
[0038] Combined with reference Figure 2 , Figure 2 Schematic diagram of the preparation principle of silicon negative electrode material 100 when the grafted group is epoxy group. Taking epoxy group as an example, the step of preparing pre-treated particles includes: pre-treating the core 10 with raw materials including oxidant and epoxy compound.
[0039] Exemplarily, the oxidant may be concentrated sulfuric acid, hydrogen peroxide, concentrated nitric acid, potassium permanganate, etc. The epoxy compound may be silane coupling agent KH-560, epichlorohydrin, ethylene oxide, epoxy resin, etc. Wherein, the mass ratio of the oxidant: the epoxy compound = 1: (1-2). Exemplarily, the pretreatment temperature is 60°C to 120°C. Specifically, the pretreatment temperature may be values such as 60°C, 80°C, 100°C, 120°C, and any values between the above values. . The surface of the inner core 10 is treated with an oxidant and an epoxy compound so that the surface of the inner core 10 is grafted with epoxy groups to prepare pretreated particles.
[0040] S2. preparing a mixed raw material, wherein the mixed raw material includes pretreated particles and polyacrylic acid salt, and the polyacrylic acid salt is coated on the surface of the pretreated particles to form a polyacrylic acid layer 30 .
[0041] Exemplarily, the polyacrylate may be polyacrylic acid lithium (PAALi). In the embodiment of the present application, the polyacrylate is mixed with the pretreated particles so that the polyacrylate is attached to the outer surface of the pretreated particles, thereby forming a polyacrylic acid coating layer, and then the surface of the pretreated particles can be coated with multiple layers of polyacrylic acid (PAA) molecular chains, which is conducive to the subsequent formation of a polyacrylic acid layer 30 on the surface of the pretreated particles.
[0042] For example, the mass fraction of the polyacrylate is 1% to 2% based on the mass of the mixed raw material. Specifically, the mass fraction of the polyacrylate in the mixed raw material can be 1%, 1.5%, 2%, and any value in between.
[0043] S3, heating the mixed raw materials to prepare the modified silicon negative electrode material 100, wherein the carboxyl group of the polyacrylic acid layer 30 reacts with the grafted group under heating conditions.
[0044] In the embodiment of the present application, the mixed raw materials are heated so that the grafted groups grafted on the surface of the inner shell in the pretreated particles can chemically react with the carboxyl groups of the polyacrylate wrapped in the outer layer of the pretreated particles, thereby chemically grafting the polyacrylic acid layer 30 to the surface of the carbon material layer 13 in the inner core 10, and further achieving the chemical grafting of the polyacrylic acid layer 30 to the outer surface of the inner core 10.
[0045] Continue reading Figure 2 , wherein the grafted group is an epoxy group as an example, the epoxy group grafted on the surface of the core 10 can undergo a ring-opening reaction with the carboxyl group of the polyacrylic acid layer 30 under heating conditions, thereby obtaining a modified silicon negative electrode material wrapped in a dense network layer of polyacrylic acid (PAA). Exemplarily, when the grafted group is an epoxy group, in the step of heating the mixed raw materials, the heating temperature is 100°C to 200°C. Specifically, the heating temperature can be 100°C, 130°C, 150°C, 180°C, 200°C, and other values, as well as any values between the above values.
[0046] In the preparation method of the modified silicon negative electrode material 100 provided in the embodiment of the present application, a grafting group is formed on the surface of the carbon material layer 13 in the core 10, and then the grafting group is used to react with the carboxyl group in the polyacrylic acid layer 30 to achieve chemical grafting of the polyacrylic acid layer 30 on the surface of the core 10. Among them, the polyacrylic acid layer 30 is coated on the surface of the core 10. On the one hand, the carboxyl group on the long chain of polyacrylic acid in the polyacrylic acid layer 30 can react chemically with the surface modification group of the core 10 to form a chemical bond such as an ester group, thereby forming a two-dimensional dense network on the surface of the core 10, and the core 10 is wrapped therein to form a dense network structure. The closed network structure has a strong elastic contraction force, which is conducive to reducing the expansion rate of the silicon negative electrode particles 11 in the core 10. On the other hand, the polyacrylic acid in the polyacrylic acid layer 30 is a polyanionic polymer with good ionic conductivity, which can effectively improve the conductivity of the modified silicon negative electrode material 100, thereby effectively improving the conductivity of the negative electrode sheet prepared by it, so that the assembled battery has both high energy density and long cycle life.
[0047] The present application also provides a method for preparing a negative electrode sheet including the silicon negative electrode material 100, comprising:
[0048] P1. Provide or prepare pretreated particles, the pretreated particles include an inner core 10 and a grafted group grafted on the surface of the inner core 10, the inner core 10 includes a silicon negative electrode particle 11 and a carbon material layer 13 coated on the surface of the silicon negative electrode particle 11, the grafted group is grafted on the surface of the carbon material layer 13, and can react with a carboxyl group.
[0049] P2. Mix the raw materials including pretreated particles and polyacrylic acid salt to obtain negative electrode slurry, provide a negative electrode current collector, set the negative electrode slurry on the surface of the negative electrode current collector to obtain a pole piece to be processed, wherein the polyacrylic acid salt is coated on the surface of the pretreated particles to form a polyacrylic acid layer 30.
[0050] In the embodiment of the present application, the raw material including the pre-treated particles is first taken, and then polyacrylic acid salt is added during homogenization, and mixed to obtain the negative electrode slurry. In the present embodiment, the negative electrode slurry can be disposed on the surface of the negative electrode current collector by coating.
[0051] P3. Heating the electrode to be treated to obtain a negative electrode, wherein the carboxyl group of the polyacrylic acid layer 30 reacts with the grafted group under heating conditions.
[0052] In an embodiment of the present application, the electrode to be treated is baked at a certain temperature so that the grafted groups grafted on the surface of the carbon material layer 13 in the pretreated particles can react with the carboxyl groups of the polyacrylic acid in the polyacrylic acid layer 30, thereby achieving chemical grafting of the polyacrylic acid layer 30 to the surface of the carbon material layer 13 in the inner core 10.
[0053] In the following, the modified silicon negative electrode material 100 provided in the embodiment of the present application and the battery prepared by using the modified silicon negative electrode material 100 are described in combination with specific embodiments. Among them, the core 10 is a silicon negative electrode particle 11 coated with a carbon material layer 13, wherein the silicon negative electrode particle 11 is a silicon-carbon material particle, and the silicon-carbon material is prepared by processes such as feeding, crushing, screening, CVD (Chemical Vapor Deposition, chemical vapor deposition) coating, carbonization, crushing, screening, and demagnetization.
[0054] Example 1 to Example 9
[0055] Embodiments 1 to 9 all provide a battery, which is prepared according to the following steps:
[0056] Preparation of pretreated particles: Take the material of the core 10, use concentrated sulfuric acid oxidant and silane coupling agent KH-560 epoxy compound to pretreat the surface of the core 10 at 80°C, so that the surface of the core 10 is grafted with epoxy groups to obtain pretreated particles.
[0057] Preparation of the electrode to be processed: Mix the pre-treated particles and lithium polyacrylate to obtain a mixed raw material as a negative electrode slurry, and apply the negative electrode slurry on the surface of the copper foil to obtain the electrode to be processed. The polyacrylate is coated on the surface of the pre-treated particles to form a polyacrylic acid layer 30. The mass fraction of lithium polyacrylate in the mixed raw material and the molecular weight of lithium polyacrylate in the mixed raw material in Examples 1 to 9 are shown in Table 1.
[0058] Preparation of negative electrode sheet: The electrode sheet to be processed is baked and then subjected to roller pressing to obtain the negative electrode sheet, wherein the epoxy groups grafted on the surface of the core 10 in the pretreated particles and the carboxyl groups in the polyacrylic acid layer 30 coated on the surface of the pretreated particles undergo a ring-opening reaction under baking conditions.
[0059] Preparation of battery: The positive electrode layer material is homogenized, coated, and rolled to obtain a positive electrode sheet. The positive electrode sheet, the prepared negative electrode sheet, and other materials such as the separator are wound and assembled to obtain a small cylindrical battery.
[0060] Comparative Example 1
[0061] Comparative Example 1 provides a battery, which is prepared according to the following steps:
[0062] Preparation of negative electrode sheet: Mix raw materials including the core 10 to obtain negative electrode slurry, apply the negative electrode slurry on the surface of copper foil, bake at 60°C to 90°C, and then roll-press to obtain negative electrode sheet. The core 10 in comparative example 1 is made of the same material as the core 10 in embodiment 1.
[0063] Preparation of battery: The positive electrode layer material is homogenized, coated, and rolled to obtain a positive electrode sheet. The positive electrode sheet, the prepared negative electrode sheet, and other materials such as the separator are wound and assembled to obtain a small cylindrical battery.
[0064] Table 1 Mass fraction of lithium polyacrylate in the mixed raw material and molecular weight of lithium polyacrylate in the mixed raw material in Examples 1-9
[0065] Mass fraction of lithium polyacrylate Molecular Weight of Lithium Polyacrylate Example 1 0.5% 300,000 Example 2 1% 300,000 Example 3 1.5% 300,000 Example 4 2% 300,000 Example 5 3% 300,000 Example 6 1.5% 50,000 Example 7 1.5% 100,000 Example 8 1.5% 500,000 Example 9 1.5% 600,000
[0066] The batteries in Examples 1-9 and Comparative Example 1 were tested for performance, and the results are shown in Table 1 below.
[0067] Table 2 Performance of the batteries of Examples 1-8 and Comparative Example 1
[0068]
[0069]
[0070] As can be seen from Table 1, compared with the battery of Comparative Example 1, the modified silicon negative electrode material formed by coating with a polyacrylic acid layer in Examples 1 to 9 has a lower negative electrode sheet full charge expansion rate, and the assembled battery has a higher energy density and a higher capacity retention rate after cyclic use. The experimental results show that the use of a polypropylene layer to modify the inner core containing silicon negative electrode particles can effectively reduce the expansion rate of silicon negative electrode particles, thereby effectively reducing the full charge expansion rate of the negative electrode sheet. In addition, the polyacrylic acid layer in the modified silicon negative electrode material can effectively improve the conductivity of the negative electrode sheet, thereby improving the energy density and cycle life of the assembled battery.
[0071] In addition, by comparing Examples 1 to 5, compared with Example 1 and Example 5, the negative electrode sheets prepared in Examples 2 to 4 have a lower negative electrode full charge expansion rate, and the assembled battery has a higher energy density and a higher cycle capacity retention rate. The experimental results show that in the process of preparing the negative electrode sheet, controlling the mass fraction of polyacrylate in the mixed raw material formed by the pretreated particles and lithium polyacrylate to be 1% to 2% can improve the energy density and cycle life of the assembled battery.
[0072] By comparing Example 3 with Examples 6 to 9, compared with Example 6 and Example 9, the negative electrode sheets prepared in Example 3, Example 7 and Example 8 have a lower negative electrode full charge expansion rate, and the assembled battery has a higher energy density and a higher cycle capacity retention rate. The experimental results show that in the process of preparing the negative electrode sheet, controlling the molecular weight of the polyacrylate to 100,000 to 500,000 can improve the energy density and cycle life of the assembled battery.
[0073] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. A modified silicon negative electrode material, characterized in that: It comprises a core and a shell layer, wherein the core comprises silicon negative electrode particles and a carbon material layer coated on the surface of the silicon negative electrode particles, and the shell layer is a polyacrylic acid layer, and the polyacrylic acid layer is coated on the surface of the carbon material layer.
2. The modified silicon negative electrode material according to claim 1, characterized in that: The polyacrylic acid layer is chemically grafted onto the surface of the carbon material layer.
3. The modified silicon negative electrode material according to claim 1, characterized in that: The material of the silicon negative electrode particles includes at least one of pure silicon, silicon carbon and silicon oxygen.
4. A method for preparing a modified silicon negative electrode material, characterized in that: include: Providing or preparing pretreated particles, the pretreated particles comprising a core and a grafting group grafted on the surface of the core, the core comprising a silicon negative electrode particle and a carbon material layer coated on the surface of the silicon negative electrode particle, the grafting group being grafted on the surface of the carbon material layer and capable of reacting with a carboxyl group; preparing a mixed raw material, wherein the mixed raw material comprises the pretreated particles and polyacrylic acid salt, wherein the polyacrylic acid salt is coated on the surface of the pretreated particles to form a polyacrylic acid layer; The mixed raw material is heated to prepare a modified silicon negative electrode material, wherein the carboxyl group of the polyacrylic acid layer reacts with the grafted group under the heating condition.
5. The method for preparing the modified silicon negative electrode material according to claim 4, characterized in that: The grafted group includes at least one of an epoxy group, an amino group, and a hydroxyl group.
6. The method for preparing the modified silicon negative electrode material according to claim 5, characterized in that: The grafted group is an epoxy group, and the step of preparing the pretreated particles comprises: pretreating the core using a raw material comprising an oxidant and an epoxy compound.
7. The method for preparing the modified silicon negative electrode material according to claim 6, characterized in that: The mass ratio of the oxidant to the epoxy compound is 1:(1-2).
8. The method for preparing the modified silicon negative electrode material according to claim 6, characterized in that: The pretreatment temperature is 60°C to 120°C.
9. The method for preparing the modified silicon negative electrode material according to claim 6, characterized in that: In the step of heating the mixed raw materials, the heating temperature is 100°C to 200°C.
10. The method for preparing the modified silicon negative electrode material according to claim 4, characterized in that: Calculated by the mass of the mixed raw materials, the mass fraction of the polyacrylate is 1% to 2%.
11. The method for preparing a modified silicon negative electrode material according to claim 4, characterized in that: The molecular weight of the polyacrylic acid in the polyacrylic acid layer is 100,000 to 500,000.
12. A negative electrode sheet, characterized in that: It includes a negative electrode current collector and a negative electrode layer covering the surface of the negative electrode current collector, wherein the material of the negative electrode layer includes a modified silicon negative electrode material, and the modified silicon negative electrode material is the modified silicon negative electrode material according to any one of claims 1 to 3, or is a modified silicon negative electrode material prepared by the preparation method of the modified silicon negative electrode material according to any one of claims 4 to 11.
13. A battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet as claimed in claim 12.
Citation Information
Patent Citations
Polymer modified silicon-carbon composite material and application thereof
CN109742369A
Silicon-based negative electrode material and lithium ion battery containing silicon-based negative electrode material
CN111769266A
Modified conductive polymer coated silicon-based anode material and preparation method and application thereof
CN111785949A
Ion / electron double-conduction material for modified positive electrode of solid-state battery and preparation method of ion / electron double-conduction material
CN112615007A
Negative electrode material, secondary battery and electric equipment
CN117012930A
Cited By
Silicon negative electrode plate, preparation method thereof and lithium ion battery
CN120356902A
Silicon-carbon composite material and preparation method thereof, battery monomer, battery device and power utilization device
CN121546046A